ANALISIS DAN IMPLEMENTASI PEMASARAN DIGITAL PADA UMKM TINY PRESENT - Sentoso, Antony; Lady; Marninda, Caroline; Angela; Wijaya, Charlie; Martinus, Titan (Transpublika Publisher, 2023)
A celebration is always associated with giving hampers as a means of socializing. Often, there are many businesses engaged in this field, one of which is Tiny Present. In an increasingly digital era that makes business people also adapt to the use of social media in its operations. Tiny Present has used the Instagram platform as a means of promotion and required the development of other platforms to optimize this business. The author conducted an interview with the owner and literature study on the implementation that is suitable for this MSME and the author decided to implement the use of LinkTree, WhatsApp Business, and landing pages that are considered capable of increasing brand awareness and sales from Tiny Present.